Using Nyquist Stability Criterion for Determining the Stability of Open and Closed-Loop Control Systems - B. Hamid, Abdelrahim (Gezira Journal of Engineering and Applied Sciences; Vol 11 No 1 (2016), 2018)
The Nyquist stability criterion has been applied in polar plots of the open-loop transfer function. In analyzing multiple-loop systems, the inverse transfer functions sometimes may be used in order to permit graphical analysis, this avoids much of numerical calculations. Nyquist stability criterion used to determine the stability of closed-loop system from its open-loop frequency response and open-loop poles.      In this paper we represented some illustrative examples of the stability analysis for control systems using Nyquist stability criterion. In examining the stability of open and closed-loop control systems, we found that three possibilities can occur.